Design and validation of an online interventions protocol for post-divorce adjustment - Abbas Sadeghi; Mahmoud Goudarzi; Parviz Karimisani (مجله علوم روانشناختی)
Background: Studies have shown that individuals who experience divorce often face challenges in adjusting to their new circumstances and may encounter difficulties in managing emotions, coping with stress, and maintaining healthy relationships. Online interventions have emerged as a novel approach to supporting individuals in the post-divorce period. These interventions typically provide interactive resources and tools through digital platforms, offering guidance, support, and skill-building exercises to assist individuals in navigating the challenges of divorce and enhancing their psychological well-being. However, there is a gap in the existing research regarding the design and validation of online intervention protocols, particularly tailored to post-divorce adjustment. Aims: The aim of the present study was to design and validate an online intervention protocol for post-divorce adjustment. Methods: This research was conducted using a qualitative method (thematic analysis) through semi-structured interviews, with the target population consisting of all family experts in Khuzestan province. The research sample was selected using purposive sampling method. The criteria for selecting individuals included holding a doctoral degree in counseling or psychology and having a minimum of 5 years of therapeutic experience with couples and families. The interview data were analyzed in three stages: open coding, axial coding, and selective coding, using MAXQDA software. Results: In the developed protocol, interventions were categorized into three sections: self, children, and emotions and stress. The self-section comprised five topics: stress and anxiety management, anger management, resilience, communication with the ex-spouse, and remarriage. The children section included five topics: investing in children's future, interactions regarding parenting, interactions with families, remarriage, and interactions with children during holidays and celebrations. The emotions and stress section encompassed two topics: forgiving the ex-spouse and accepting divorce and reality. Conclusion: Considering the positive validation results of the designed protocol, its utilization for post-divorce adjustment during contagious diseases that require non-face-to-face services will aid in the adjustment of these individuals. It is recommended that mental health professionals take steps to expand its implementation in the field of mental health.